Book review: In a rain of dust: Death, deceit and the lawyer who busted big asbestos by David Kinley - Singer, Michal (New Agenda: SA Journal of Social and Economic Policy, 2026)
David Kinley’s In a Rain of Dust is an unusually gripping work of legal, environmental, and social history − a book that transforms one of South Africa’s most devastating and least discussed industrial tragedies into a vivid, morally urgent narrative.